A simple favor [videorecording (DVD)] - Kendrick, Anna; Lively, Blake; Golding, Henry, 1987-; Bell, Darcey (Lions Gate Entertainment, 2018)
A mommy vlogger seeks to uncover the truth behind her best friend Emily's sudden disappearance from their small town.